Fishing-effort response dynamics in fisheries for short-lived invertebrates. (1st November 2018) - Ben-Hasan, A.; Walters, C.; Louton, R.; Christensen, V.; Sumaila, U.R.; Al-Foudari, H.
Abstract: In complex dynamic systems like fisheries, recognizing fishing-effort responses is as critical as understanding the biology of the exploited species for making sensible management decisions. In highly seasonal fisheries, it is theoretically possible for an "interannual bionomic equilibrium" to develop under open-access, where fleet dynamics may result in balanced year-to-year harvesting due to decreasing income per time fishing as biomass declines, without endangering the sustainability of the stock. However, in some conditions, this interannual bionomic equilibrium can be pathologically low leading to overfishing and amplification of extinction risks. Here we draw three cases from short-lived and fast-growing invertebrate fisheries to illustrate two distinct effort response dynamics: (a) fishing-effort responses that lead to healthy interannual bionomic equilibrium; and (b) fishing-effort responses in which fishing remains profitable over the entire season, hence, allowing fishing fleets to maintain a high fishing-effort throughout the season. Analyzing long-term within-year catch and effort data, we found that both Gulf of Mexico shrimp and North Territory giant crab fisheries are likely currently at healthy interannual bionomic equilibria, while certain socioeconomic drivers enable the Kuwait shrimp fishery to maintain high effort through the entire shrimping season. Our findings suggest that input controls are less effective in short-lived invertebrate fisheries that exhibit fishing-effort proportional to declining stock abundance. Conversely, if not regulated, the abundance-insensitive fishing-effort response could pose biological risks and habitat destruction. Therefore, we emphasize that in common-property seasonal fisheries, fishing-effort responses be scrutinized to distinguish factors that might undermine resource sustainability. Highlights: Recognition of fishing-effort responses is as critical as understanding the biology of the exploited species. We identify two distinct fishing-effort response dynamics in highly seasonal fisheries. The first response parallels stock biomass trend due to strong bionomic feedback. The second response is biomass-insensitive that remains high at low stock size owing to certain socioeconomic factors.